Antimicrobial peptides (AMPs) as drug candidates: a patent review (2003–2015). (2nd June 2016) - Kosikowska, Paulina; Lesner, Adam
ABSTRACT: Introduction : Antimicrobial peptides (AMPs) represent the large group of endogenous compounds widely distributed in nature. Due to their broad spectrum of antibiotic activity, as well as anti-inflammatory and immunomodulatory properties, AMPs became a model for the discovery of novel antimicrobial drugs that could answer the problem of the increasing antibiotic resistance of pathogenic microorganisms. Areas covered: The review represents a comprehensive analysis of patents and patent applications from the year 2003 to 2015 referring to the therapeutic use of AMPs. The article highlights the general trends in the design, potential mode of action, and methods of biological evaluation of AMPs. Expert opinion: The existing discord between the upcoming list of antimicrobial peptides claimed in the patents or related scientific articles as the potent drug candidates and the frequent failures of AMPs in clinical trials emphasize the need of a better understanding of their pleiotropic nature and mechanisms of host defense in general. Nevertheless, the encouraging examples of AMPs already introduced into the market, like Polymyxin or Fuzeon®, give some reason for optimism that development of AMPs as a novel class of antibiotics is still considered viable.